Chemically deposited cubic SnS thin films for solar cell applications. (1st December 2016) - Chalapathi, U.; Poornaprakash, B.; Park, Si-Hyun
Highlights: Growth of cubic SnS thin films by chemical bath deposition technique. Effect of bath temperature on the growth and properties of cubic SnS thin films. Effect of Na2 S2 O3 concentration on the growth and properties of cubic SnS thin films. Bath temperature of 45 °C and Na2 S2 O3 concentration of 0.125 M are optimized conditions. Abstract: Cubic SnS is a promising absorber material for thin film heterojunction solar cells. In this paper, we report the fabrication of cubic SnS films by chemical bath deposition technique. The effects of bath temperature and Na2 S2 O3 concentration on the properties of the films were investigated. Films deposited at different bath temperatures showed a slightly Sn-rich composition. An increase in the bath temperature from 25 °C to 65 °C caused increase in the crystallite size from 17 nm to 70 nm. An increase in the bath temperature to up to 45 °C resulted in an improvement in the grain size, whereas a further increase in the bath temperature resulted in a slight decrease in the grain size. The band gap of the films decreased from 1.74 eV to 1.68 eV with increasing bath temperature. The films deposited from solutions on increasing the Na2 S2 O3 concentration showed a slight improvement in the atomic percentage of S. The films deposited with a Na2 S2 O3 concentration of 0.125 M showed a compact and uniform morphology with a grain size of ∼1 μm. With an increase in the Na2 S2 O3 concentration from 0.125 M to 0.175 M in the solution, the band gap of the films increased from 1.73 eV to 1.82 eV. The films exhibited p-type electrical conductivity. The films deposited with the Na2 S2 O3 concentration of 0.125 M showed a higher hole mobility of 75.1 cm 2  V −1  s −1 . Thus, the above results showed that a bath temperature of 45 °C and Na2 S2 O3 concentration of 0.125 M are the optimum conditions for obtaining near-stoichiometric cubic SnS films with good structural, microstructural, optical and electrical properties.